Precision Analysis of Vibration Energy Flux in Angular Connection of Plates - CIEŚLIK, Jacek; PIECZARA, Janina (Archives of Acoustics, 2008)
Qualitative assessment of energy balance in mechanical systems is possible by the use of energy flow descriptors and observation of energy density distribution in the mechanical structure. The aim of the analysis was quantitative estimation of vibration energy transmitted through the welded connections of ribbed plates. The structural intensity was used as the parameter for the analysis. Obtained results of calculation gave the quantitative information on amount of energy transmitted, reflected, stored and the damped in welded joints of plates. Analyzed cases were intentional to show the utility of intensity method in diagnostics of joints in mechanical constructions. Calculation results were verified experimentally by measurements of stress with application lock-in-thermography.